PENINGKATAN KAPASITAS MITIGASI IKLIM BERBASIS PARTISIPASI MASYARAKAT MELALUI IMPLEMENTASI BIOPORI DI DESA KARANGREJO - Aqilatur Raisyah; Naela Husna; Nadia Septiana; Roy Martin; Nailah Tsany Aristawati; Dinda Aulia Ramadhani; Daniel Prima Nugroho; Suroto; Yus Andini Bhekti Pertiwi; Muhammad Rafid Alamsyah; Azri Natsir Sipayung; Nurfina Qurrota A'yun (PT. Hasba Edukasi Mandiri, 2026)
Global climate change has led to an increase in natural disasters in Indonesia. This situation requires efforts to strengthen environmental resilience that directly involve the community. One such program is the Climate Village Program (Proklim). Proklim plays a crucial role in promoting climate change adaptation and mitigation efforts at the community level. However, the implementation of this program still faces challenges, primarily due to the community’s limited knowledge and capacity in managing the environment. Therefore, this activity focuses on the application of Biopore Percolation Pits (LRB) technology in Karangrejo Village, Karanganyar Regency. Biopore pits are a simple technology for processing organic waste into compost, improving water infiltration, reducing waterlogging, and helping to curb environmental pollution in a sustainable manner. The objective is to help address organic waste issues and improve water infiltration into the soil. The method employed is a participatory approach, involving the community through awareness campaigns and hands-on biopore creation activities. The results of the initiative demonstrate increased community understanding and participation in organic waste management. It is hoped that this program will encourage the community to sort organic waste and process it into compost. As a result, this initiative can strengthen environmental resilience at the local level and support the success of the Proklim program and Proklim’s Sustainable Development Goal (SDG) 13.